2019
DOI: 10.1155/2019/7346863
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of Gut Microbiota, Concentration of Short-Chain Fatty Acids, and Inflammatory Markers Associated with Elevated Body Fat, Overweight, and Obesity in Female Adolescents

Abstract: Background and Aims. Overweight is ever more prevalent in the pediatric population, and this cardiometabolic factor can be associated with inflammatory markers, gut microbiota composition, and short-chain fatty acid (SCFA) concentrations. The aim of this study is to evaluate to what extent the abundance of gut microbiota phyla, SCFA concentrations, and inflammatory markers are associated with elevated body fat percentage (BF%), overweight, and obesity in female adolescents. Methods. An experimental and compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 38 publications
3
31
0
5
Order By: Relevance
“…These findings are in consonance with the systematic review study carried out by [ 49 ] where biomarker as hs-CRP was correlated with physical activity and subjects' dietary habits. In addition, an association between overweight (assessed by BMI), high BF%, and central fat accumulation in adolescents were also identified by Miranda et al [ 50 ] and Elizondo-Montemayor et al [ 21 ]. In the present study, results showed that the girls from the Inactive & Sedentary LS class displayed the higher levels of blood pressure (SBP and DBP) and TNF- α concentration.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…These findings are in consonance with the systematic review study carried out by [ 49 ] where biomarker as hs-CRP was correlated with physical activity and subjects' dietary habits. In addition, an association between overweight (assessed by BMI), high BF%, and central fat accumulation in adolescents were also identified by Miranda et al [ 50 ] and Elizondo-Montemayor et al [ 21 ]. In the present study, results showed that the girls from the Inactive & Sedentary LS class displayed the higher levels of blood pressure (SBP and DBP) and TNF- α concentration.…”
Section: Discussionmentioning
confidence: 66%
“…The overweight or obese adolescents with elevated BF% (G3) displayed higher values of blood pressure, changes in biochemical parameters, and higher concentrations of hs-CRP, when compared to the eutrophic with adequate BF% (G1). In a previous study conducted by our group [ 50 ], adolescents from the EUT & High %BF and OW-OB & High BF groups displayed a higher concentration of central, visceral fat, and leptin than the EUT & Adequate %BF group. These results highlight the role of BF% in the prevalence of cardiometabolic risk factors.…”
Section: Discussionmentioning
confidence: 89%
“…Several cross-sectional studies have reported positive associations between fecal SCFAs levels and obesity [ 16 , 17 , 18 , 19 , 20 ]. For example, a community-based study of 441 Colombian adults aged 18–62 years demonstrated that higher fecal butyrate, acetate, propionate and total SCFAs were associated with BMI, body fat, and waist circumference [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, not all epidemiological studies that support positive associations between SCFAs and adiposity measures also suggest the potential involvement of gut microbiota [ 13 , 16 , 17 , 19 , 20 ]. Whereas a recent meta-analysis of case-control studies found no evidence of association between obesity and phyla richness [ 16 ], other studies found that higher fecal SCFAs were associated with lower microbiota diversity, as well as higher gut permeability, Firmicutes/Bacteriodetes ratio and cardiometabolic disease-associated taxa [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation